Water Oxidation on Porphyrines: A First-principles Study - Arvidsson, Adam (My University, 2014)
Research on electrocatalysts for water oxidation into hydrogen and oxygen is of great importance in order to combat global warming and make sustainable technology more efficient and economically viable. This thesis studies water oxidation on a cobalt-porphyrine catalyst with density functional theory (DFT), using the Quantum ESPRESSO software. Reaction energies for the two different porphyrines: the porphyrine and the hangman-porphyrine in vacuum were calculated and found to be in agreement with previous results. After addressing the question of how water affects the oxygen evolution reaction (OER) on porphyrines many new challenges were identified. Using ab-initio molecular dynamics with a temperature, configurations were sampled and the configurations of minimum energy were found. This resulted in an unexpected reaction energy landscape. The properties of the water in this model were further investigated by studying the diffusion and radial distribution function of bulk water. It turns out that water in this model is more mobile than expected and appears to be in a liquid phase even at a temperature of 50K. The unexpected energy landscape is attributed to the water model due to it's unphysical behaviour.
Keywords: Fysik; Beräkningsfysik; Elektronstruktur; Kemisk fysik; Physical Sciences; Computational physics; Electronic structure; Chemical physics